Fatca and its key provisions and the issues of its application in Peru - Sheppard Castillo, Karen (2014)
As an answer to the international tax evasion problem, the U.S. Congress issued the Foreign Account Tax Compliance Act – Fatca. This Act aims to promote tax compliance among citizens and U.S. residents holding foreign bank accounts. To this effect, Fatca requires Foreign Financial Institutions to enter into an agreement with the Internal Revenue Service (IRS) to provide the IRS information about the identity and the status of the bank accounts held by US persons. Entities not willing to enter into an agreement with the IRS will be subject to a 30% withholding on U.S. sourced income regardless of whether the income is tax exempt. The application of this Act in our country brings a lot of concern regarding some issues, such us extraterritoriality, bank secrecy, the application of civil and criminal law. Since the effective date of implementation of Fatca is July 1, 2014, we understand that an official opinion concerning these issues and the possibilityto enter into an Intergovernmental Agreement with the U.S. government will be forthcoming in the following months.